2020
DOI: 10.1186/s42358-020-00136-6
|View full text |Cite
|
Sign up to set email alerts
|

The musculoskeletal impairment negatively impacts the quality of life of children and adolescents with psoriasis

Abstract: Background The severity of nail disease, the presence of arthralgia and fatigue are predictors of development of psoriatic arthritis (PsA) in patients with psoriasis (Pso). In children, little is known about the musculoskeletal (MSK) impairment in patients with Pso and its effect on health-related quality of life (HRQoL). Objectives To determine the frequencies of pain and MSK inflammation (i.e., arthritis, enthesitis, and sacroiliitis) among children and adolescents with Pso and its relationship to HRQoL and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
2
0
3
Order By: Relevance
“…Для раннего дебюта заболевания характерно развитие олиго-или полиартрита с поражением мелких суставов и наличием антинуклеарных антител [6]. При появлении симптомов артрита в более позднем возрасте наблюдаются формирование энтезита, спондилоартрита, поражения аксиальных суставов, наличие антигена HLA-B27 [6][7][8].…”
Section: особенности клинической картиныunclassified
See 2 more Smart Citations
“…Для раннего дебюта заболевания характерно развитие олиго-или полиартрита с поражением мелких суставов и наличием антинуклеарных антител [6]. При появлении симптомов артрита в более позднем возрасте наблюдаются формирование энтезита, спондилоартрита, поражения аксиальных суставов, наличие антигена HLA-B27 [6][7][8].…”
Section: особенности клинической картиныunclassified
“…было проведено исследование среди детей с псориазом в возрасте от 2 до 16 лет. Отмечена высокая частота болевого синдрома со стороны опорно-двигательного аппарата (персистирующая боль в проекции суставов, боль в поясничном и крестцово-подвздошном отделах позвоночника в покое и при пальпации), ассоциированного с тяжелым течением псориатического процесса на коже, поражением ногтевых пластинок и повышенной утомляемостью [7]. Авторы исследования отметили у пациентов с псориазом пониженный болевой порог.…”
Section: особенности клинической картиныunclassified
See 1 more Smart Citation
“…However, musculoskeletal symptoms, including pain and fatigue, are highly prevalent in patients with PsO, having a negative impact on their physical function and quality of life [8]. These symptoms have been described not only in adults but also in children and adolescents with PsO [9]. In a more detailed way, Merola et al [8] reported an increased prevalence of musculoskeletal symptoms in a 60-month follow-up study of newly diagnosed adult patients with PsO (47.1% at baseline, 48.2% after 12 months, and 82.1% after 60 months).…”
Section: Introductionmentioning
confidence: 99%
“…a negative impact on the quality of life (QoL), all children and adolescents with psoriasis should be screened for arthritis. 28 A four-question evaluation of clinical history has been proposed to screen for arthritis in children with psoriasis (Box 1). Assessment of adolescents using the Psoriasis Epidemiology Screening Tool (PEST) has also been proposed, together with the referral of patients to a rheumatology department if any signs or symptoms of arthritis are reported.…”
mentioning
confidence: 99%